Visitors' awareness of ICZM and WTP for beach preservation in four European Mediterranean regions. (January 2016) - Marzetti, S.; Disegna, M.; Koutrakis, E.; Sapounidis, A.; Marin, V.; Martino, S.; Roussel, S.; Rey-Valette, H.; Paoli, C.
Abstract: This paper discusses the results of a multi-country survey about private stakeholders' contribution to coastal preservation. It was conducted in four coastal sites of Greece, Italy and France, in order to collect information about beach visitors' perception of Integrated Coastal Zone Management (ICZM) and their willingness to pay (WTP) for beach preservation, intended here as defence from erosion. In order to find out whether ICZM perception is a determinant of WTP, regression analysis is applied. Results show that in these sites respondents have a low level of information about the nature of ICZM, despite local authorities having implemented some ICZM strategies for preserving the coast. Nevertheless, those who are informed about ICZM have a higher probability of paying for beach preservation. This suggests to policymakers that promoting public awareness about ICZM may increase the probability of paying. Finally, some categories of visitors, such as women and young and middle-aged people, have a higher probability of paying than men and older people, thus suggesting a more sensitive attitude to beach preservation. Therefore, policy-makers should also pay attention to the categories of visitors less likely to pay.